Acute administration of oxycodone, alcohol, and their combination on simulated driving—preliminary outcomes in healthy adults - Babalonis, Shanna; Coe, Marion A.; Nuzzo, Paul A.; Lofwall, Michelle R.; Ali, Nur; Sloan, Paul A.; Fanucchi, Laura C.; Walsh, Sharon L. (Psychopharmacology, 2021)
Rationale Epidemiological data indicate that drivers testing positive for an opioid drug are twice as likely to cause a fatal car crash; however, there are limited controlled data available. Objectives The primary aim of this study was to assess the effects of a therapeutic dose range of oxycodone alone and in combination with alcohol on simulated driving performance. Methods Healthy participants ( n = 10) completed this within-subject, double-blind, placebo-controlled, randomized outpatient study. Six 7-h sessions were completed during which oxycodone (0, 5, 10 mg, p.o.) was administered 30 min before alcohol (0, 0.8 g/kg (15% less for women), p.o.) for a total of 6 test conditions. Driving assessments and participant-, observer-rated, psychomotor and physiological measures were collected in regular intervals before and after drug administration. Results Oxycodone alone (5, 10 mg) did not produce any changes in driving outcomes or psychomotor task performance, relative to placebo ( p > 0.05); however, 10 mg oxycodone produced increases in an array of subjective ratings, including sedation and impairment ( p < 0.05). Alcohol alone produced driving impairment (e.g., decreased lateral control) ( p < 0.05); however, oxycodone did not potentiate alcohol-related driving or subjective effects. Conclusions These preliminary data suggest that acute doses of oxycodone (5, 10 mg) do not significantly impair acuity on laboratory-based simulated driving models; however, 10 mg oxycodone produced increases in self-reported outcomes that are not compatible with safe driving behavior (e.g., sedation, impairment). Additional controlled research is needed to determine how opioid misuse (higher doses; parenteral routes of administration) impacts driving risk.